International﻿ fisheries threaten globally endangered sharks in the Eastern Tropical Pacific Ocean: the case of the Fu Yuan Yu Leng 999 reefer vessel seized within the Galápagos Marine Reserve - Elisa Bonaccorso (Nature Portfolio, 2021)
Abstract Shark fishing, driven by the fin trade, is the primary cause of global shark population declines. Here, we present a case study that exemplifies how industrial fisheries are likely depleting shark populations in the Eastern Tropical Pacific Ocean. In August 2017, the vessel Fu Yuan Yu Leng 999, of Chinese flag, was detained while crossing through the Galápagos Marine Reserve without authorization. This vessel contained 7639 sharks, representing one of the largest seizures recorded to date. Based on a sample of 929 individuals (12%), we found 12 shark species: 9 considered as Vulnerable or higher risk by the IUCN and 8 listed in CITES. Four species showed a higher proportion of immature than mature individuals, whereas size-distribution hints that at least some of the fishing ships associated with the operation may have been using purse-seine gear fishing equipment, which, for some species, goes against international conventions. Our data expose the magnitude of the threat that fishing industries and illegal trade represent to sharks in the Eastern Tropical Pacific Ocean.